1988
DOI: 10.1113/jphysiol.1988.sp017182
|View full text |Cite
|
Sign up to set email alerts
|

Conduction of neural impulses in human mechanoreceptive cutaneous afferents.

Abstract: SUMMARY1. It was the aim of the present study to isolate and identify the components underlying the human sensory compound action potential and to study their axonal conduction velocities and refractory periods. For this purpose the technique of percutaneous microneurography was combined with intradermal electrical stimulation of nerve fibre terminals. Sixty-four median and ulnar nerve afferents innervating the glabrous skin of the digits were isolated and type identified.2. The range of axonal conduction velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…The microneurographic technique used in this study is biased towards large-diameter axons, yet the functional properties among fast-conducting afferents are not related to their conduction velocity, i.e. to the axon diameter (Mackel, 1988). Relevant skin areas of the thigh were stimulated by stroking hand movements while the electrode was moved in minute steps until single unit activity was observed in the neural signal.…”
Section: Neurophysiological Techniquementioning
confidence: 99%
“…The microneurographic technique used in this study is biased towards large-diameter axons, yet the functional properties among fast-conducting afferents are not related to their conduction velocity, i.e. to the axon diameter (Mackel, 1988). Relevant skin areas of the thigh were stimulated by stroking hand movements while the electrode was moved in minute steps until single unit activity was observed in the neural signal.…”
Section: Neurophysiological Techniquementioning
confidence: 99%
“…4 suggests a grouping of the present reflexes into early-and mid-latency components, there was no statistically significant difference in reflex magnitude (P ϭ 0.46) between early (25-70 ms)-and mid (70 -120 ms)-latency reflexes. The broad range of conduction velocities of individual cutaneous afferents (20 -91 m/s in the upper limb) (Kakuda 1992;Knibestol 1973;Macefield et al 1989;Mackel 1988;Vallbo 1971) further complicates any separation of individual reflexes based on latency differences alone. As our experimental techniques also did not allow us to determine whether transcortical pathways mediated any of the reflex responses, we had no firm basis on which to separate the short-latency reflex responses into early-or mid-latency reflexes.…”
Section: Reflex Latency and Reflex Classificationmentioning
confidence: 99%
“…These and other studies in humans and animals have shown (1) that the sensory fields of RA units (Meissner corpuscles) are small and sharply demarcated, whereas those of PC units (Pacini corpuscles) are large and poorly delineated 18,21,26 ; (2) that the RA units at threshold are sensitive to sinusoidal vibration of 5-40 Hz and PC units to vibration of 60-300 Hz 19,32,33,39,42 ; (3) that the threshold to indentation force is similar in RA units and PC units 23 ; (4) that the Meissner corpuscles are placed superficially in the epidermis and the Pacini corpuscles deep in the dermis or subcutis 31,38 ; (5) that the density of Meissner corpuscles increases distally in the fingers, whereas the density of PC corpuscles remains more or less constant in the hand 20 ; (6) that dynamically sensitive slowly adapting receptors have small sensory fields, and that they are situated superficially in the skin; and (7) that the conduction velocities of afferent fibers are similar in the range of large myelinated fibers. 17,25,36 Though microneurography may be used to investigate function of individual receptors in pathological states, such as wallerian degeneration and regeneration 14,35 and diabetes mellitus, 37 the technique is not suitable to delineate the extent of neuropathic processes, due to sampling difficulties when studying single nerve fibers and receptors. The method used in our work applies tactile stimuli to groups of receptors in the skin and relies on electronic averaging technique to record the CSAP from associated nerve fibers.…”
Section: Findings At Tactile Stimulation As Related To Othermentioning
confidence: 99%
“…8,10 Thus our findings are in agreement with other studies that the largest fibers innervating mechanoreceptors in the skin are in the A␣ range. 31 In most previous microneurographical studies, the conduction velocities were calculated from the distal innervation site to the recording site using an electrical current to activate the nerve fiber, 25,35,36 whereas we have excluded the distal part of the nerve by recording the CSAPs at two sites along the nerve. The distal part of the nerve fiber introduces a source of error into the calculation of the conduction velocity, due to the distal reduction in diameter and loss of myelin, which may vary among different fibers.…”
Section: Findings At Tactile Stimulation As Related To Othermentioning
confidence: 99%